Genetic Divergence of Sweet Pepper in Bangladesh - Akter, Limu; Hossain, Md. Mokter; Quamruzzaman, A K M; Habibur Rahman, Md.; Abdur Rahim, Md.; Khatun, Rahima (European Journal of Applied Sciences, 2024)
The study of genetic divergence in sweet pepper is essential for enhancing crop yield, quality, and adaptability, especially in regions like Bangladesh where agriculture plays a critical role in the economy. The present investigation was carried out at the research farm of the Olericulture division, Horticulture Research Centre, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh to estimate genetic divergence in 21 sweet pepper genotypes based on fourteen characters using Mahalanobis’s D2 statistics during winter 2017-18 in randomized complete block design with three replications. The results revealed significant genetic variability, indicating the presence of diverse genetic resources within the cultivated 21 sweet pepper genotypes. Cluster analysis grouped the accessions into distinct clusters, reflecting their genetic relationships and divergence. The study highlights specific genotypes with desirable traits that can be utilized in breeding programs to develop superior sweet pepper varieties. Cluster II had the maximum number (14) of genotypes and clusters I and III were composed of only two genotypes. The highest intra-cluster distance was observed in cluster II (1.286), containing fourteen genotypes and the lowest intra-cluster distance (0.056) was observed in cluster III having two genotypes. A higher inter-cluster distance was observed between clusters III and IV (14.090) and clusters I and IV (14.040) indicating the genotypes in these clusters were more diverged than those of other clusters. Cluster II exhibited maximum highest mean for fruit length at the green stage, fruit length at the mature stage and desirable minimum value for days to 50% flowering while the second highest mean values for days to last harvest, number of fruit/plant, weight of fruit/plant, average fruit weight, total number of fruit/plot, plot yield, fruit yield, while cluster IV exhibited the highest mean values for the number of fruit/plant, weight of fruit/plant, total number of fruit/plot, plot yield, fruit yield and one desirable lowest mean for days to last harvest. Therefore, more emphasis should be given to clusters II and IV for selecting genotypes as parents for crossing which may produce new recombinants with desired traits.